Phage Targeting Streptococcus mutans In Vitro and In Vivo as a Caries-Preventive Modality - Amit Wolfoviz-Zilberman; Reut Kraitman; Ronen Hazan; Michael Friedman; Yael Houri-Haddad; Nurit Beyth (MDPI AG, 2021)
Dental caries is a common infectious disease worldwide. Current conventional therapies lack specific antimicrobial effects against Streptococcus mutans, a key bacterium that induces caries. A promising alternative approach is bacteriophage (phage) therapy. Recently, SMHBZ8 phage targeting S. mutans was isolated and characterized. The aim of this study was to evaluate the caries-prevention efficacy of SMHBZ8 using in vitro and in vivo caries models. Hemi-mandibles dissected from euthanized healthy mice were subjected to caries-promoting conditions in vitro. Jaws treated with phage therapy in suspension and in formulation with a sustained-release delivery system showed no carious lesions, similar to control and chlorhexidine-treated jaws. Subsequently, SMHBZ8 phage suspension also prevented carious lesion development in a murine caries model in vivo. In both models, caries lesions were analyzed clinically and radiographically by µCT scans. This study shows how SMHBZ8 phage therapy targeting S. mutans can serve as an efficient caries-prevention modality, in suspension or with a sustained-release delivery system, by in vitro and in vivo mouse models.